Content-analysis of modern horror films (Actual Problems of Psychology in Educational Institutions, 2022)
The article is devoted to the comprehension of the psychological content of the most popular horror films for 2016-2017 years. Using the content-analysis of the video sequence of ten cinematography`s works for certain categories, there were established some unconscious factors, which determine what do the modern man afraid of the most.